American Health and Wellness in Archaeology and History - Hutchinson, Dale L. (Book collections on Project MUSE., 2022)
Looking back on this history from the perspective of the contemporary landscape of healthcare and wellness in the United States, Hutchinson points out that weaknesses in the system that became apparent amid the COVID-19 pandemic were the result of changes that have been unfolding since the founding of the nation"--